KAJIAN KEBIJAKAN DAN STRATEGI PEMERINTAH DALAM UPAYA PERLINDUNGAN TENAGA KERJA LOKAL DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Saleh, Chairul (BISMA: Jurnal Bisnis dan Manajemen, 2016)
workers, should be started from the standardization of competence and understanding of language and culture, objective and transparent certifications, strong commitment to the welfare of workers and adequate health insurance. In addition there should be strict rules related to discipline and commitment as well as the workers agreed rules related to piracy of labor and industrial relations in this case, the government became supervisor and perform kontrol. Some industries that should be prioritized to be developed in order to absorb the lokal workforce large enough and creating differentiation, the first is Agro Industries for processing agricultural products are abundant in East Java, such as tobacco, coffee, chocolate, seafood and horticulture. Secondly, processing industries, both made of metal, bamboo, stone, wood and other lokal minerals. The growth of processing industries will create new business units that will encourage a lot of new entrepreneurs. Therefore, a priority skill that should be given to the lokal force or labor force is the skill in the field of aquaculture, and processing, as well as plant management. The technology required to support the accelerated development of the industry, according to respondents apart Appropriate Technology (TTG) for people who will be the supplier (second layer) of the company, also advanced technologies that will get support from the government, because according to respondents, the lokal government must have some sort enterprises (incorporated district), which acts as the marketer of the products produced by the community, especially for the export market. Keywords : Lokal workforce, Asean Economic Community (AEC)